Plano de ação para atuação da Fundação Universidade Federal de Mato Grosso do Sul no contexto da Estratégia Nacional de Investimentos e Negócios de Impacto (ENIMPACTO) - Mariana Ribeiro de Assuncao (2021)
Impact businesses seek to combine profit-making originated from the offer of products and services with the explicit purpose of providing social and/or environmental solutions, so that the private sector can add efforts to the initiatives of governments and philanthropic organizations in combating persistent problems in areas such as health, housing, education, among others. To strengthen this type of enterprise, the National Strategy for Impact Investments and Businesses (ENIMPACTO) was created, which aims to foster an impactful environment in Brazil. ENIMAPCTO is operated by the Impact Investments and Businesses Committee, whose objectives, established by Decree nº. 9.977/2019, seek to increase the supply of capital, increase the number of impact businesses, strengthen intermediary organizations and the regulatory/institutional environment and promote data generation. In the impact ecosystem, universities are part of the group of intermediary organizations, whose role is to drive impact investments and businesses, through connections, training, knowledge, among other relevant functions. This study sought to identify how the Federal University of Mato Grosso do Sul (UFMS) fits into the impact environment and what actions the institution can adopt to expand its performance in order to strengthen impact businesses. The research is characterized as exploratory and descriptive and was conducted using a qualitative approach. Data collection took place through documentary and bibliographic research, in addition to semi-structured interviews, carried out through an electronic form, with key people at UFMS and at the ENIMPACTO Committee. For the data treatment, content analysis was used, with the help of graphics generated by the Iramuteq software. The results showed that UFMS operates based on entrepreneurship and innovation, but still does not have a specific institutional plan to support businesses with a clearly defined impact, despite already having some actions aimed at this field. An action plan was proposed for the institution to strengthen its performance in the impact ecosystem, through its performance in teaching, research and extension activities.